Determination of the Effect of Home Care Fee (HCF) Practice on the Hopelessness and Life Satisfaction Levels of Families Having an Individual with Disabilities: Konya Sample (Journal of Asian Development Studies, 2018)
Aim of this study is to determine effects of home care services on disabled individuals and their families’ hopelessness and life satisfaction level. An observational research model, that is, a complementary research model was mainly used in this study. A questionnaire form developed by the researcher to collect the opinions of families receiving home care service, the Hopelessness Scale created by Beck (1963) and the Life Satisfaction Scale improved by Diener et al. (1985) were used.  Data was gathered through face-to-face interviews with the families of disabled individuals living in Konya Selçuklu, Meram, and Karatay. In light of these findings, it was suggested the psycho-social support system for both disabled individuals and their families should be improved, a professional caring team should be created for families to provide support especially related to self-care and psychological illnesses, and social support educations should be arranged to strengthen the mothers and women; families should be informed and their awareness should be raised about organization of families and caring commission members visiting families in certain intervals  should inform families about caring techniques.